Sketching user experiences - Greenberg, Saul (Morgan Kaufmann, 2012)
Sketching Working Experience: The Workbook provides information about the step-by-step process of the different sketching techniques. It offers methods called design thinking, as a way to think as a user, and sketching, a way to think as a designer. User-experience designers are designers who sketch based on their actions, interactions, and experiences. The book discusses the differences between the normal ways to sketch and sketching used by user-experience designers. It also describes some motivation on why a person should sketch and introduces the sketchbook. The book reviews the different sketching methods and the modules that contain a particular sketching method. It also explains how the sketching methods are used. Readers who are interested in learning, understanding, practicing, and teaching experience design, information design, interface design, and information architecture will find this book relevant. Features standalone modules detailing methods and exercises for practitioners who want to learn and develop their sketching skills Extremely practical, with illustrated examples detailing all steps on how to do a method Excellent for individual learning, for classrooms, and for a team that wants to develop a culture of design practice Perfect complement to Buxton's Sketching User Experience or any UX text Author-maintained companion website at http://grouplab.cpsc.ucalgary.ca/sketchbook/